O Divino, o patrimônio e a cidade: uma análise de modulações culturais provocadas por eventos críticos - José Rogério Lopes; André Luiz da Silva; Rodrigo Manoel Dias da Silva (Ciências Sociais Unisinos)
The article examines cultural modulations in a devotional celebration in the city of São Luiz do Paraitinga (SP), Brazil, impacted by a critical event (flood) that hit the town in January 2010. The flood brought down part of the cultural heritage of the town, which was related to the achievement of the traditional Feast of the Saint Ghost. This loss allowed several assemblages religious and cultural policies emerged in the recovery process of the town, producing flows that have introduced new referents for the reinvention of the feast. Here, we seek to describe and analyze the dynamics of these assemblages, indicating the importance of cultural heritage for the affirmation of social esteem of the town and its people.